DIGITAL METER OF REACTIVITY FOR USE DURING ZERO-POWER PHYSICS TESTS AT THE KRŠKO NPP - Lengar, Igor; Trkov, Andrej; Kromar, Marjan; Snoj, Luka (Journal of Energy Technology, 2024)
A part of nuclear fuel is exchanged during an outage in a NPP, with an influence on the reactor characteristics. The parameters of the new reactor core are determined with nuclear design calculations and must be experimentally verified during reactor start up. For accurate determination of these characteristics, a device for measuring reactivity is necessary. The key tool for the performance of zero-power physics (start-up) tests at the Krško NPP is the digital meter of reactivity (DMR), developed in the 1980s at the Reactor Physics division of the Jožef Stefan Institute, in Ljubljana, Slovenia. It was the first digital device to be used within a wide range of operating conditions for the measuring of reactivity. These conditions also include measuring reactivity in a deeply subcritical reactor, which enables the DMR to determine the integral and differential worth of control banks during their insertion into the core. This new method was named ’the rod-insertion method’. The performance and development of the DMR is presented in this paper. Its unique characteristics are described with the example of the rod insertion method. Also presented are examples of measurements during the start-up physics tests at the Krško NPP.